Pulmonary Arterial Hypertension in Primary Amyloidosis. (June 2016) - Cirulis, Meghan M.; Emerson, Lyska L.; Bull, David A.; Hatton, Nathan; Nativi-Nicolai, Jose; Hildebrandt, Gerhard C.; Ryan, John J.
Amyloidosis involves extravascular deposition of fibrillar proteins within tissues and organs. Primary light chain amyloidosis represents the most common form of systemic amyloidosis involving deposition of monoclonal immunoglobulin light chains. Although pulmonary amyloid deposition is common in primary amyloidosis, clinically significant pulmonary amyloidosis is uncommon, and elevated pulmonary artery pressures are rarely observed in the absence of other underlying etiologies for pulmonary hypertension, such as elevated filling pressures secondary to cardiac amyloid. In this case report, we present a patient with primary light chain amyloidosis and pulmonary arterial hypertension in the setting of pulmonary vascular and right ventricular myocardial amyloid deposition.